Sinergitas Ulama dan Umara: Artikulasi dalam Penyelesaian Kasus Sara tentang Pemasangan Lafaz Allah pada Ornamen Pohon Natal di Hotel Novita Jambi - Bahrul Ulum (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This article aims to elaborate on the response to the process of resolving the blasphemy case that occurred in one of the hotels in Jambi. There was found the installation of Allah's label on the floor of the Christmas tree ornaments. Based on studies in the field, it was found that this case included ethnicity, race, religion and class nuance cases (SARA) and it had to be resolved immediately, because it could potentially lead to religious conflict and mass amok. The results of the study show that Firstly, the Government (leader) along with its ranks and Ulama (clerics) together with Islamic Organizations responded quickly to the blasphemy event by holding meetings and agreeing that the case should be resolved immediately so as not to cause religious conflict. Secondly, both Ulama and Umara (leader) worked together and discuss (sit and talk) a quick step in resolving the case and trying to calm the public so that they did not commit vigilante acts. The synergy pattern that is intertwined and articulated here has resulted in a swift, accurate solution to the resolution of the case and can immediately restore a supportive atmosphere for the people of Jambi.